2020
DOI: 10.3390/w12072065
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of PbS NPs and Biosorption of Pb(II) by Shinella Zoogloeoides PQ7 in Aqueous Conditions

Abstract: Increasing heavy metal pollution in water continues to endanger human health. The genus Shinella has potential for heavy metal bioremediation but has rarely been studied. In this study, we report that Shinella zoogloeoides PQ7 turns black in the presence of lead ions. Transmission electron microscopy (TEM), Scanning electron microscopy–energy dispersive X-ray spectroscopy (SEM–EDS), X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) indicated that PbS nanoparticles (NPs) were synthesized by PQ7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…[160] promote the biosynthesis of iron sulfide (FeS), greigite (Fe 3 S 4 ), and pyrite (FeS 2 ) NPs. On the other hand, the extracellular biogenesis of PbS nanocrystals has been implemented using Rhodobacter sphaeroides [79] and Shinella zoogloeoides [150]. These studies demonstrated the involvement of cysteine desulfhydrase in H 2 S production and the subsequent NP formation.…”
Section: Using Bacteriamentioning
confidence: 99%
See 4 more Smart Citations
“…[160] promote the biosynthesis of iron sulfide (FeS), greigite (Fe 3 S 4 ), and pyrite (FeS 2 ) NPs. On the other hand, the extracellular biogenesis of PbS nanocrystals has been implemented using Rhodobacter sphaeroides [79] and Shinella zoogloeoides [150]. These studies demonstrated the involvement of cysteine desulfhydrase in H 2 S production and the subsequent NP formation.…”
Section: Using Bacteriamentioning
confidence: 99%
“…Commonly, green-synthesized NPs are formed at ambient to mild temperatures and atmospheric pressures. Importantly, the parameters particularly relevant to consider are the pH, organism, salt sources, biomass concentration, time, and additional reagents [41,100,137,150].…”
Section: Control Over S-np Biosynthesismentioning
confidence: 99%
See 3 more Smart Citations